1998
DOI: 10.1080/106351598260879
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and Floral Evolution of Baobabs Adansonia, Bombacaceae as Inferred From Multiple Data Sets

Abstract: The phylogeny of baobab trees was analyzed using four data sets: chloroplast DNA restriction sites, sequences of the chloroplast rpl16 intron, sequences of the internal transcribed spacer (ITS) region of nuclear ribosomal DNA, and morphology. We sampled each of the eight species of Adansonia plus three outgroup taxa from tribe Adansonieae. These data were analyzed singly and in combination using parsimony. ITS and morphology provided the greatest resolution and were largely concordant. The two chloroplast data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
202
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(213 citation statements)
references
References 56 publications
5
202
1
1
Order By: Relevance
“…The primers used to amplify matK, trnK-710F and trnK-2R, originally derived from Johnson and Soltis (1995), were the same as used by Koch et al (2001). The ITS primers amplified a region that included the 5.8S region and the flanking portions of the 18S and 26S regions (Baum et al 1998;White et al 1990). The trnL primers used corresponded to trnC and trnD from Taberlet et al (1991).…”
Section: Taxon Samplingmentioning
confidence: 99%
“…The primers used to amplify matK, trnK-710F and trnK-2R, originally derived from Johnson and Soltis (1995), were the same as used by Koch et al (2001). The ITS primers amplified a region that included the 5.8S region and the flanking portions of the 18S and 26S regions (Baum et al 1998;White et al 1990). The trnL primers used corresponded to trnC and trnD from Taberlet et al (1991).…”
Section: Taxon Samplingmentioning
confidence: 99%
“…Introduction et al, 2001), in contrast to that of oceanic islands for which long-distance dispersals have been compulsory prior to The theory of evolution for most of the continental biolocal radiations (Wagner and Funk, 1995; Francisco-Ortetas has been largely based on vicariance and speciation ga et al, 1996). However, recent biogeographical studies caused by geographical or genetic barriers (Raven and have demonstrated that transcontinental dispersals have Axelrod, 1972Axelrod, , 1974Morrone and Crisci, 1995; Sanmartin been more common than previously thought and that those events have affected a large number of angiosperm lineages (Soreng, 1990;Vargas et al, 1998;Vijverberg et al, 1999;hemisphere where species relationships are more complex and highly reticulate Coleman et al, 2003) as well as in the southern hemisphere where the species appear more geographically structured (Baum et al, 1998;Sanmartín and Ronquist, 2004). Compiled data indicate that the overwhelming predominance of long-distance dispersals over vicariances detected in austral plants, contrary to those observed in animals, might have been caused by the accumulation of those recent events in terminal taxa that could have obscured a deeper vicariance signal or just correspond to young-age lineages (Sanmartín and Ronquist, 2004).…”
mentioning
confidence: 99%
“…Many current investigations within the Andropogoneae tribe utilize the ITS1 and ITS2 regions because they are known to incorporate changes at comparatively high rates (Hershkovitz and Zimmer, 1997;Baum et al 1998). The analysis of the sugarcane dataset indicates that cluster SCCCLR1CO5E04.g (107274) contains 590 base pairs corresponding to the complete coding sequence of the ITS1-5.8S-ITS2 region, which was utilized for the parsimony analyses summarized in Table II.…”
Section: Resultsmentioning
confidence: 99%